The Impact Of Total Suspended Solid (TSS) And Containing Water Chlorophyll-A On The Fertility Level Of Jakarta Jakarta Bay Waters Using Technology Of Google Earth Engine (Gee) Clouds - Sinaga, Mardame Pangihutan; Siburian, Daniel Tony Edyt; Zega, Edward Kristian (Jurnal Ilmiah Platax, 2024)
Research on the distribution of TSS and containing water chlorophyll-a using GEE Cloud Technology in Jakarta Bay Waters was conducted from April to August 2021. Analysis was carried out using the MODIS AQUA-L3SMI satellite and Sentinel 2 TOA reflectance data. The TSS results show that it is distributed evenly (homogenously), varies, and fluctuates from the coast of Jakarta to the Waters of Jakarta Bay, namely 0-120 mg/l, while the containing water chlorophyll-a is distributed unevenly or varies, namely from April 2021 with value 0-3 mg/m3, chlorophyll-a in May 2021 almost evenly distributed with a value of 0-2 mg/m3, chlorophyll-a in June 2021 spread unevenly and fluctuating with an amount of 1-3  mg/m3, for chlorophyll-a in July 2021 was absent due to the influence of many and thick clouds. Chlorophyll-a in August 2021 spread almost evenly and varied throughout the waters amounting to 0,28 mg/m3. TSS spreads evenly (homogeneously), varies, and fluctuates around the edge of Jakarta's coastal waters down to the waters of Jakarta Bay and is not suitable for demersal fish species except zooxanthellae coral reef species. Meanwhile, the containing water chlorophyll-a is spread evenly, varies, and fluctuates. The large amount of chlorophyll-a in all waters and the high TSS will cause total death of living creatures in the waters. Image data can be used to map TSS distribution patterns and contain water chlorophyll-a in the waters of Jakarta Bay. Keywords: TSS; Containing Water Chlorophyll-a; MODIS AQUA-L3SMI Satellite; Sentinel 2 TOA reflectance data Satellite; Jakarta Bay Waters. Abstrak Penelitian sebaran TSS dan kandungan klorofil-a menggunakan Teknologi GEE Cloud di Perairan Teluk Jakarta telah dilaksanakan dari bulan April sampai dengan Agustus 2021. Analisis dilakukan dengan menggunakan satelit MODIS AQUA-L3SMI dan Sentinel 2 TOA reflectance data. Hasil TSS diperoleh bahwa menyebar merata (homogen), bervariasi, dan berfluktuasi dari pinggir pantai Jakarta sampai ke arah perairan Teluk Jakarta, yaitu 0-120 mg/l, sedangkan kandungan klorofil-a menyebar tidak merata atau bervariasi, yaitu dari bulan April 2021 dengan nilai 0-3 mg/m3, klorofil-a di bulan Mei 2021 hampir menyebar merata yang nilai 0-2 mg/m3, klorofil-a di bulan Juni 2021 menyebar tidak merata dan berfluktuasi dengan jumlah 1-3 mg/m3, untuk klorofil-a di bulan Juli 2021 tidak ada karena pengaruh awan yang banyak dan tebal, dan klorofil- a di bulan Agustus 2021 menyebar hampir merata dan bervariasi ke seluruh perairan berjumlah 0-2,8 mg/m3. TSS menyebar secara merata (homogen), bervariasi dan fluktuasi di sekitar pinggiran perairan pantai Jakarta sampai ke perairan Teluk Jakarta dan tidak cocok untuk jenis-jenis ikan demersal kecuali jenis terumbu karang zooxanthellae. Sedangkan kandungan klorofil-a nya menyebar secara merata, bervariasi dan fluktuasi. Banyaknya kandungan klorofil-a yang ada di semua perairan dan TSS nya tinggi, akan menyebabkan kematian secara total terhadap makhluk hidup di dalam perairan. Data citra dapat digunakan untuk memetakan pola sebaran TSS dan kandungan klorofil-a di wilayah perairan Teluk Jakarta. Kata kunci: TSS; Kandungan Klorofil-a; Satelit MODIS AQUA-L3SMI; Satelit Sentinel 2 TOA reflectance data; Perairan Teluk Jakarta